2009
DOI: 10.1021/om9007295
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Butadiyne to Butatrienylidene Isomerization in [Ru(HC≡CC≡CH)(PMe3)2(Cp)]+

Abstract: The butadiyne to butatrienylidene isomerization in [Ru(HCCCCH)(PMe3)2(Cp)]+ has been investigated by density functional calculations. Several possible minima have been identified on the potential energy surface for the coordinated C4H2 moiety, and a few plausible isomerization mechanisms have been analyzed by a DFT approach. The butatrienylidene complex has been found to be more stable than the butadiyne adduct by −13.1 kcal mol−1 in enthalpy and is the thermodynamically most stable species on the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 126 publications
1
16
0
Order By: Relevance
“…At present, the exact mechanistic role of acid in these reactions is unclear. Re and colleagues have examined mechanisms of proton migration from ethynylvinylidene to butatrientylidene supported by a {Ru(PMe 3 ) 2 Cp} + fragment, and proposed that the isomerization proceeds via a deprotonation/re‐protonation mechanism . In our case, it seems that the additional acid is important in promoting protonation at the terminal carbon to give the quinoidal cumulene, albeit as a transient intermediate that we have not yet succeeded in detecting spectroscopically in solution (Scheme ).…”
Section: Resultsmentioning
confidence: 80%
“…At present, the exact mechanistic role of acid in these reactions is unclear. Re and colleagues have examined mechanisms of proton migration from ethynylvinylidene to butatrientylidene supported by a {Ru(PMe 3 ) 2 Cp} + fragment, and proposed that the isomerization proceeds via a deprotonation/re‐protonation mechanism . In our case, it seems that the additional acid is important in promoting protonation at the terminal carbon to give the quinoidal cumulene, albeit as a transient intermediate that we have not yet succeeded in detecting spectroscopically in solution (Scheme ).…”
Section: Resultsmentioning
confidence: 80%
“…A theoretical study (B3LYP/LACV3P + + **) into the rearrangement of the butadiyne complex 17) has revealed the presence of a similar mechanistic pathway. [24] The calculations indicate that a direct 1,4-hydrogen shift from 13 c to give 17 is unlikely and that a ethynylvinyli-…”
Section: Ruthenium Vinylidene Complexesmentioning
confidence: 95%
“…24 In the case of d 8 metal complexes, a bimolecular mechanism has been proposed for the alkyne to vinylidene isomerization on the fragment {RhCl-(P i Pr 3 ) 2 } via formation of the dimeric d 6 11 However, other researchers have gathered theoretical and experimental evidence in support of an alternative mechanism for this process which does not involve dimeric species. 13 , and no H/D scrambling was observed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7d, 24 On the other hand, the 1,3-H migration (pathway B) entails oxidative addition of the coordinated alkyne to give a hydrido−alkynyl complex, which then isomerizes via 1,3-H shift. The influence of the chloride anion in these routes has been considered, namely, pathways AI-Cl and AII-Cl (stable intermediates in pathway B were not found).…”
Section: ■ Introductionmentioning
confidence: 99%